First report of thyroid goiter in the marine ornamental fish Gramma brasiliensis - Araújo-Silva, Sérgio Leandro; de Castro, Maria Alcina Martins; Mendes, Ricardo Evandro; Pelisser, Giovana; da Rocha, Vanessa Martins; Ferrarezi , José Victor Safadi; Ozório, Renata Ávila; Tsuzuki, Mônica Yumi (Brazilian Journal of Veterinary Medicine, 2024)
Enlargement of the thyroid gland is referred to as goiter. In captive fish, goiter may be associated with iodine deficiency in water or diet, exposure to goitrogenic factors such as a high environmental nitrate concentration or water treatment with ozone. This report describes the occurrence of goiter in a marine ornamental fish raised in a research laboratory, the Brazilian basslet Gramma brasiliensis. From 2016 to 2023, we observed progressively growing tumour-like masses in the pharyngeal cavity and along the gill arches of approximately 20 adult individuals. This abnormal growth impaired the ingestion of food and caused dyspnoea, leading the animals to death within a few months after the first appearance of the mass. The samples were submitted to histological analyses, which revealed moderate to severe, diffuse, hypertrophy and hyperplasia of thyroid follicular cells with most lacking colloids. This is the first report of goiter in the Brazilian basslet. Although it is not clear why this condition develops in this species, we recommend keeping nitrate levels to a minimum and monitoring water iodine concentrations regularly until future studies investigate the possible causes and adequate treatment for this species.